Senior-Loken Syndrome: A Rare Case Report of A Novel NPHP4 Gene Mutation in A Child From Bangladesh: Senior-Loken Syndrome - Akbar, Romana; Ali, Asif; Al Mamun, Abdullah; Begum, Afroza (Journal of Pediatric Nephrology, 2025)
Background and Aim: Senior Loken syndrome describes patients with nephronophthisis along with retinal dystrophy. The first signs of renal involvement include polyuria and polydipsia, which occur due to impaired urinary concentration capabilities. Nephronophthisis progresses to end-stage renal disease by the age of 20. Retinal abnormalities can range from severe infantile retinal dystrophy to the more typical form of retinitis pigmentosa. Other associated features of this syndrome include skeletal and dermatological abnormalities, as well as cerebellar issues. Case Presentation: Here, we reported a case of Senior‒Loken syndrome with polyuria, polydipsia, and nocturnal enuresis followed by the features of advanced renal disease, such as growth retardation and moderate anemia. He was also myopic and demonstrated tessellated fundus during the fundoscopic examination. Conclusion: To date, there are no case reports published in the Bangladeshi medical literature regarding this rare autosomal recessive disorder among pediatric patients. Therefore, this case report aims to increase awareness among clinicians to detect these patients early, as the management implemented may prevent or delay the need for renal replacement therapy and preserve eyesight